Demographic and health surveillance: longitudinal ethical considerations - Margaret Carrel; Stuart Rennie
Longitudinal data gathered from health surveillance, when combined with detailed demographic information, can provide invaluable insight into disease outcomes. Many such surveillance sites exist in the developing world, particularly in Asia and sub-Saharan Africa, and focus on diseases such as HIV/AIDS, cholera, malaria and tuberculosis. The indistinct positions of such surveillance systems, often inhabiting an area between research, treatment and population health monitoring, means that the necessity of and responsibility for ethical oversight is unclear. This regulatory vacuum is further compounded by a lack of attention to longitudinal surveillance systems in ethics literature. In this paper, we explore some key ethical questions that arise during demographic and health surveillance in relation to ethical principles of beneficence, respect for persons and justice: health-care provision, informed consent and study sustainability.